TINGKAT PENGETAHUAN TERHADAP SIKAP PASIEN DIABETES MELLITUS PADA PENGGUNAAN VCO DI PUSKESMAS RAWA MEKAR JAYA - Fahriati, Andriyani Rahmah; Rubiana, Amalia Cinta; Oktovina, Magdalena Niken; Hartono, Irwan; Aulia, Gina; Saputri, Dea Maulidi; Fu'adah, Intan Tsamrotul (PHRASE (Pharmaceutical Science) Journal, 2025)
Diabetes mellitus (DM) is a group of metabolic disorders characterized by hyperglycemia accompanied by abnormal carbohydrate, fat, and protein metabolism. Diabetic foot ulcers are a common complication of diabetes. Diabetic wound care is not solely handled with antibiotics; wound care is mandatory. In diabetic wound care practices, the use of VCO (Virgin Coconut Oil) is often chosen because it maintains wound moisture and is more economical. Knowledge and attitudes are important factors to analyze in supporting therapy. The purpose of this study was to analyze the level of knowledge and attitudes of diabetes mellitus patients regarding the use of VCO at the Rawa Mekar Jaya Community Health Center. This study used a prospective observational research method. Patient samples were selected using a non-random sampling technique (purposive sampling) and must meet the inclusion criteria. The sample consisted of 121 DM patients. The results showed that 78 respondents had good knowledge, of which 62 respondents (51.2%) had a good attitude towards the use of VCO, and 16 respondents (13.2%) showed a poor attitude. Meanwhile, there were 43 respondents with less knowledge, of which 16 respondents (13.2%) had a good attitude and 27 respondents (22.3%) had a less than good attitude. It is known that respondents who have good knowledge, their attitudes towards the use of VCO also increase, as indicated by the results of the bivariate analysis, where the p-value is 0.000 (p 0.05) so it is concluded that there is a relationship between the level of knowledge and the attitudes of diabetes patients on the use of VCO about their treatment.